Real Analysis

Winter 2025

Part 1:

Sets

(See Chapter 1 in Book of Proof)

The central objects in mathematics are sets. A set is a collection of things. The things in a set are called elements.

Sets

Often, we denote a set by simply writing all the elements between \(\{\}\) ("curly braces") separated by commas. For example,

\[\{1,2,4,5\}\]

is the set with four elements, these elements being \(1,2,4,\) and \(5\).

We often give sets names, these will frequently be a single capital roman letter, for example, \[B = \{1,2,4,5\}.\]

To express the statement "\(x\) is an element of \(A\)" we write \(x\in A\). Thus, given the set \(B\) defined above, we see that \(1\in B\) is a true statement, and \(3\in B\) is a false statement.

We will also write \(x\notin A\) to for the statement "\(x\) is not an element of \(A\)."

Equality of sets

Two sets \(A\) and \(B\) are equal (they are the same set) if they contain exactly the same elements, that is, the following two statements hold:

If \(x\in A\), then \(x\in B\).

If \(x\in B\), then \(x\in A\).

In this case we write \(A=B\).

Important example:

Important example: Consider the sets \(A=\{1,2,2,3\}\) and \(B=\{1,2,3\}\). We can easily see that every element of \(A\) is an element of \(B\), and every element of \(B\) is an element of \(A\). Thus

\[\{1,2,2,3\}=\{1,2,3\}.\]

An element is either in a set or it is not. Sets cannot contain multiple copies of an element.

Subsets

Given two sets \(A\) and \(B\), if every element of \(A\) is also an element of \(B\), then we say that \(A\) is a subset of \(B\), and write \(A\subset B\) or \(A\subseteq B\) (these both mean the exact same thing). For example,

\[\{1,2\}\subset\{1,2,4,5\}\]

but \(\{1,2,3\}\) is not a subset of \(\{1,2,4,5\}\) since \(3\in\{1,2,3\}\) and \(3\notin\{1,2,4,5\}\)

Note that the statement "\(A=B\)" can be rewritten as "\(A\subset B\) and \(B\subset A.\)" This will be very useful later.

Ellipsis notation

The set of integers is denoted \(\mathbb{Z}\). The set of positive integers, also called the natural numbers or the naturals, is denoted \(\mathbb{N}\) or \(\mathbb{Z}^{+}\). 

We will sometimes write sets like \(\mathbb{N}\) and \(\mathbb{Z}\) with ellipsis notation, as follows,

\[\N=\{1,2,3,\ldots\}\qquad \Z = \{\ldots,-2,-1,0,1,2,3,\ldots\}\]

In this notation, we list the first several elements of a set, until there is an apparent pattern, then write an ellipsis (...). After the ellipsis we write the final element in the pattern. If no element is written after the ellipsis, then the list of elements goes on without end.

Examples.

  • \(\{2,4,6,8,\ldots\}\) is the set of even positive integers.
  • \(\{3,7,11,15,\ldots,43\}=\{3,5,7,11,15,19,23,27,31,35,39,43\}\)

Problems with ellipsis notation

Consider the set

\[C:=\{2,4,8,\ldots\}.\]

Questions:

Is \(16\in C\)?    Is \(14\in C\)?

What is the pattern? Is the \(n\)th term in the sequence \(2^{n}\) or \(n^2-n+2\) or something else?

It's not clear!

Suppose \(N\in\mathbb{N}\) and define the set

\[D:=\{2,4,6,\ldots,2N\}.\] If \(N=5\), then

\[D = \{2,4,6,\ldots,10\}=\{2,4,6,8,10\}\]

but if \(N=2\), then

\[D = \{2,4,6,\ldots,4\}(?)\]

We will interpret this set as \(\{2,4\}\). 

Set builder notation

Let \(A\) be a set, and \(S(x)\) denote a statement whose truth value depends on \(x\in A\). The set of \(x\in A\) such that \(S(x)\) is true is denoted

\[\{x\in A : S(x)\}\quad\text{or}\quad \{x\in A\mid  S(x)\}\quad\text{or}\quad \{x : x\in A\text{ and }S(x)\}.\]

Both the colon and the vertical line are read as "such that" or "with the property that."

Example. Consider the set of even positive integers:

\[\{x\in\mathbb{N} : x\text{ is even}\}.\]

This would be read:

"The set of \(x\) in the natural numbers such that \(x\) is even."

Using the notation from the above definition we have \(A=\N\) and \(S(x)\) is the statement "\(x\) is even"

Set builder notation

More generally, let \(A\) be a set. For each \(x\in A\) let \(f(x)\) be an expression that depends on \(x\) and \(S(x)\) denote a statement whose truth value depends on \(x\in A\). The set of all elements of the form \(f(x)\) with the property that \(x\in A\) and \(S(x)\) is true is denoted

\[\{f(x) : x\in A\text{ and }S(x)\}.\]

Example. Consider the set of even positive integers:

\[\{2x: x\in \N\}.\]

In the notation of the above definition we have  \(A=\N\), \(f(x) = 2x\), and \(S(x)\) is true for all \(x\in\N\).

 

Using set builder notation we can disambiguate the sets from two slides prior:

\[\{2^{n} : n\in\mathbb{N}\}\quad\text{and}\quad\{n^2-n+2 : n\in\mathbb{N}\}.\]

Examples. 

  • \(\{2n-1 : n\in\N\text{ and }n\leq 5\} = \{1,3,5,7,9\}\)
  • \(\{25-4n : n\in\N\text{ and }n\leq 10\text{ and } n>5\} = \{1,-3,-7,-11,-15\}\)

Consider the set 

\[\{x\in\mathbb{R} : x^{2}+1 = 0\}.\]

There does not exist a real number \(x\) such that \(x^{2}+1=0\), and hence this set does not contain any elements!

 

The set containing no elements is called the empty set. The empty set is denoted \(\varnothing\) or \(\{\}\).

Part 2:

Proofs and Logic

(See Chapters 2,4,5 & 6 in Book of Proof)

Proposition 1. \(\{n\in\mathbb{Z} : n+1\text{ is odd}\} = \{2n : n\in\mathbb{Z}\}.\)

Proving sets are equal.

Proof. First we will show that \(\{n\in\mathbb{Z} : n+1\text{ is odd}\} \subset \{2n : n\in\mathbb{Z}\}.\) Let \(m\in\{n\in\mathbb{Z} : n+1\text{ is odd}\}\) be arbitrary. This implies that \(m+1\) is odd, that is, there exists \(k\in\Z\) such that \(m+1=2k+1.\) Subtracting \(1\) from both sides we deduce \(m=2k\), and hence \(m\in \{2n : n\in\Z\}.\)

Next, we will show \(\{2n:n\in\mathbb{Z}\}\subset\{n\in\mathbb{Z} : n+1\text{ is odd}\}\).

Let \(p\in\{2n:n\in\mathbb{Z}\}\) be arbitrary. Then, there exists \(q\in\mathbb{Z}\) such that \(p=2q\), and hence \[p+1 = 2q+1.\] Since \(q\in\mathbb{Z}\), we conclude that \(p+1\) is odd, and hence

\(p\in\{n\in\mathbb{Z} : n+1\text{ is odd}\}.\) \(\Box\)

Definition. An integer \(n\) is even if there exists an integer \(k\) such that \(n=2k\). An integer \(n\) is odd if there exists an integer \(p\) such that \(n=2p+1\).

Proposition 2. If \(n\in\Z\) is odd, then \(n^{2}\) is odd.

Proving implications (Direct proof)

\(A : n\) is odd

\(B : n^{2}\) is odd

We wish to prove the implication \(A\Rightarrow B\). We will use a direct proof, that is, we will assume \(A\), argue directly to \(B\).

Proof. Suppose \(n\in\Z\) is odd. By definition, this means that there exists \(k\in\Z\) such that \(n=2k+1\). This implies

\[n^{2} = (2k+1)^{2} = 4k^{2}+4k+1 = 2(2k^{2}+2k)+1.\]

Since \(2k^{2}+2k\) is an integer, we conclude that \(n^{2}\) is odd. \(\Box\)

Proposition 3. Suppose \(n\in\Z\). If \(n^{2}\) is even, then \(n\) is even.

Proving implications (Contrapositive proof)

\(A : n^{2}\) is even

\(B : n\) is even

We wish to prove \(A\Rightarrow B\). Instead, we can prove the equivalent statement \((\sim\! B)\Rightarrow(\sim\!A)\), where \(\sim\!A\) denotes the negation of the statement \(A\). The statement \((\sim\! B)\Rightarrow(\sim\!A)\) is called the contrapositive of the statement \(A\Rightarrow B\).

Proof. Suppose \(n\in\Z\) is not even. This implies that \(n\) is odd. By the previous proposition we see that \(n^{2}\) is odd, and therefore \(n^{2}\) is not even. \(\Box\)

In words, the contrapositive of the above proposition takes the form:

Suppose \(n\in\Z\). If \(n\) is not even, then \(n^{2}\) is not even.

Proposition 4. Suppose \(a,b,c\in\Z\). If \(a^{2}+b^{2}=c^{2}\), then either \(a\) is even or \(b\) is even.

Proving implications (Proof by contradiction)

\(A : a^{2}+b^{2}=c^{2}\)

\(B : a\) is even or \(b\) is even

We wish to prove \(A\Rightarrow B\). Instead, we can prove the equivalent implication \(A\wedge(\sim\!B)\Rightarrow C\wedge(\sim\!C)\) for any(!) statement \(C\). That is, we assume \(A\) and \(\sim\!B\), and we argue that some statement \(C\) and it's negation \(\sim\!C\) both hold. This is called proof by contradition.

The statement we will actually prove is:

If there are integers \(a,b,c\) such that both \(a\) and \(b\) are odd, and        \(a^{2}+b^{2}=c^{2}\), then \(4\) divides \(2\). Since it is obvious that \(4\) does not divide 2, we are proving \[A\wedge(\sim\!B)\Rightarrow C\wedge(\sim\!C)\] where \(C:\) 4 divides 2.

(Note that \(A\Rightarrow B\) is the same as \((\sim\!A)\vee B\), hence, in proof by contradiction, we begin by assuming the negation \(A\wedge(\sim\!B)\) of the statement we are trying to prove.)

Proposition 4. Suppose \(a,b,c\in\Z\). If \(a^{2}+b^{2}=c^{2}\), then either \(a\) is even or \(b\) is even.

Proof. Assume toward a contradiction that there are integers \(a,b,c\) such that \(a\) and \(b\) are both odd, and \(a^{2}+b^{2}=c^{2}\). By definition there exist integers \(k,p\in\Z\) such that \(a=2k+1\) and \(b=2p+1\). Note that

\[c^{2} = a^{2}+b^{2} = (2k+1)^{2}+(2p+1)^{2} = 4k^{2}+4k+4p^{2}+4p+2.\] From this we see that \(c^{2}\) is even, and by the previous proposition \(c\) is even. By definition there exists \(m\in\Z\) such that \(c=2m\). Using the above equation we see that

\[4(k^{2}+k+p^{2}+p)+2 = c^{2} = (2m)^{2} = 4m^{2}.\] Rearranging we have

\[4(m^{2}-k^{2}-k-p^{2}-p) = 2.\]

This last equation implies that \(2\) is divisible by \(4\). Since we know that \(2\) is not divisible by \(4\), this gives the desired contradiction. \(\Box\)

Proposition 3. Suppose \(n\in\Z\). If \(n^{2}\) is even, then \(n\) is even.

Contrapositive vs. Contradiction

Proof. Assume toward a contradiction that \(n\) is not even and \(n^{2}\) is even. This implies that \(n\) is odd, that is \(n=2k+1\) for some \(k\in\Z\). Squaring, we obtain

\[n^{2} = 4k^{2}+4k+1=2(2k^{2}+2k)+1.\]

Since \(2k^{2}+2k\) is an integer, this shows that \(n^{2}\) is odd. This contradicts the fact that \(n^{2}\) is even.\(\Box\)

Proof by contradiction: \(A\wedge(\sim\!B)\Rightarrow C\wedge(\sim\!C)\)

Contrapositive: \((\sim\!B)\Rightarrow(\sim\!A)\)

Fake proof by contradiciton: \(A\wedge(\sim\!B)\Rightarrow A\wedge(\sim\!A)\)

Moral: If your proof by contradiction concludes with \(\sim\!A\), then you should use proof by contrapositive instead!

Universal quantifier

\(A : n^{2}\) is even

\(B : n\) is even

Note that \(A\) and \(B\) below are not statements. They're truth value depends on \(n\).

These are more precisely called open sentences (or predicates or propositional functions). They should really have variables

\(A(n) : n^{2}\) is even

\(B(n) : n\) is even

Proposition 3. Suppose \(n\in\Z\). If \(n^{2}\) is even, then \(n\) is even.

Recall the proposition:

Now, Proposition 3 can be more precisely written as \[\forall\,n\in\Z,\ A(n)\Rightarrow B(n).\]

Where the symbol \(\forall\) stands for "for all" or "for every," and is called the universal quantifier.

Note that \(A(n) : n^{2}\) is even, is false unless \(n\in\Z\).

 

Recall that for false statements \(A\), the statement \(A\Rightarrow B\) is true for any statement \(B\). (In this case \(A\Rightarrow B\) is called a vacuously true statement.)

 

Thus, in the statement \(\forall\,n\in\Z,\ A(n)\Rightarrow B(n)\) the universal quantifier isn't really necessary. It would be very common to see Proposition 3 written as

 

Proposition 3. If \(n^{2}\) is even, then \(n\) is even.

 

The universal quantifier "For all \(n\in\Z\)" is there, it's just not written.

 

Moral: In math we often omit the universal quantifier before an implication.

Existential quantifier

To say that an open sentence \(A(x)\) is true for all \(x\) in a set \(X\) we use the universal quantifier:

\[\forall\,x\in X,\ A(x).\]

In math, we would write this using words:

"For all \(x\in X\), \(A(x)\) is true."

To say that an open sentence \(A(x)\) is true for at least one \(x\) in a set \(X\) we use the existential quantifier \[\exists\, x\in X,\ A(x).\] In words:

"There exists \(x\in X\) such that \(A(x)\) is true."

Universally quantified statements may be more common, but here is an example of a statement that is not:

"The polynomial \(x^{5}+5x^3+10\) has a real root."

Do you see that this statement is of the form \(\exists\, x\in X,\ A(x)\). What are the set \(X\) and the open sentence \(A(x)\)?

Order of quantifiers

Consider the following two statements:

\(A:\ \) For every even \(n\in\N\) there exists an odd \(m\in\N\) such that \(m>n\).

\(B:\ \) There exists odd \(m\in\N\) such that for all even \(n\in\N\), it is true that \(m>n\).

 

Because it sounds better in English, we will often write \(B\) as

\(B:\ \) There exists odd \(m\in\N\) such that \(m>n\) for all even \(n\in\N\).

Let \(E\) denote the set of even natrual numbers, and let \(D\) denote the set of odd natural numbers. Using symbols, we can write \(A\) and \(B\) as follows: \[A: \forall\, n\in E,\ \exists\,m\in D,\ m>n\]

\[B: \exists\,m\in D,\ \forall\, n\in E,\ m>n\]

Moral: \(A\) is true, and \(B\) is false. The order of the quantifiers matters. You must think hard to figure out the meaning of a statement, there is no shortcut!

Proving universally quantified statements

Every universally quantified statement can be converted to an implication:

\[\forall\, x\in X,\ A(x)\]

is the same as

\[(x\in X)\Rightarrow A(x)\]

Thus, to prove this statement we take an "arbitrary" element \(x\in X\), then reason that \(A(x)\) is true for that \(x\). The proof looks like

 

Proof. Let \(x\in X\) be arbitrary.

\[\vdots\]

\[\vdots\]

Therefore, \(A(x)\). \(\Box\)

For example, let's say we want to prove the following statement:

 

Proposition. For every even number \(n\in\N\), the number \(n^2+1\) is odd.

We might start checking cases:

If \(n=2\), then \(n^2+1=5\). (\(n=2\cdot 1\), then \(n^2+1=2\cdot 2+1\))

If \(n=4\), then \(n^{2}+1=17\). (\(n=2\cdot 2\), then \(n^2+1=2\cdot 8+1\))

\(\vdots\)

But this will never prove the claim.

Instead, we take an arbitrary even number \(n\in\N\).

Now, using only our assumptions that \(n\) is an even natural number, we must argue that \(n^2+1\) is odd.

First, note that there exists \(k\in\N\) such that \(n=2k\). 

Next, note that \(n^2+1 = 4k^2+1 = 2(2k^2)+1\).

Since \(2k^2\) is an integer, we conclude that \(n^2+1\) is odd.

We might start checking cases:

If \(n=2\), then \(n^2+1=5\). 

If \(n=4\), then \(n^{2}+1=17\).

\(\vdots\)

But this will never prove the claim.

For example, let's say we want to prove the following statement:

 

Proposition. For every even number \(n\in\N\), the number \(n^2+1\) is odd.

Proof. Let \(n\in\N\) be an arbitrary even number. This implies that \(n=2k\) for some integer \(k\), and thus

\[n^2+1 = (2k)^{2}+1 = 4k^{2}+1 = 2(2k^{2})+1.\]

Since \(2k^2\) is an integer, we conclude that \(n^2+1\) is odd. \(\Box\)

Proving quantified statements

Theorem 1.18. For every positive real number \(x\) there exists a natural number \(n\) such that \(n>x.\)

Proposition. For every \(\varepsilon>0\) there exists \(m\in\N\) such that \(\dfrac{1}{m}<\varepsilon\).

Proof. Let \(\varepsilon>0\) be arbitrary. Note that \(1/\varepsilon\) is a positive real number. By the Theorem 1.18 there exists a natural number \(m\in\N\) such that \(m>\frac{1}{\varepsilon}\). This implies

\[\frac{1}{m}<\varepsilon.\]

The following is an important property of the natural numbers and the real numbers. We will prove it later, but for now we will assume it is true.

\(\Box\)

Proving quantified statements

Proposition. For every \(\varepsilon>0\) there exists \(m\in\N\) such that \(\dfrac{1}{m}<\varepsilon\).

Proof. Assume toward a contradiction that there exists \(\varepsilon>0\) such that \(\varepsilon\leq \dfrac{1}{m}\) for all \(m\in\mathbb{N}\). This implies that \(\dfrac{1}{\varepsilon}\geq m\) for all \(m\in\N\). By Proposition 1.18 there is a natural number \(k\in\N\) such that \(k>\dfrac{1}{\varepsilon}\). This is a contradiction. \(\Box\)

What would it look like if we tried to prove this statement by contradiction?

Statement: \(\forall\,\varepsilon>0,\ \exists\,m\in\N,\ \dfrac{1}{m}<\varepsilon.\)

Negation: \(\exists\,\varepsilon>0,\ \forall\,m\in\N,\ \dfrac{1}{m}\geq\varepsilon.\)

In words, the negation might read:

There exists \(\varepsilon>0\) such that \(\varepsilon\leq \dfrac{1}{m}\) for all \(m\in\mathbb{N}\).

Part 3:

Properties of \(\mathbb{R}\)

(See Chapter 1 in Spivak)

The algebraic properties of the real numbers \(\mathbb{R}\):

(P1) (Associativelaw for addition) \[\forall\,a,b,c\in\mathbb{R},\ a+(b+c) = (a+b)+c.\]

(P2) (Existence of an additive idenity) \[\exists\, 0\in\mathbb{R},\ \forall a\in\mathbb{R},\ a+0=0+a=a.\]

(P3) (Existence of additive inverses) \[\forall\, a\in\mathbb{R},\ \exists -a\in\mathbb{R},\ a+(-a) = (-a)+a = 0.\]

(P4) (Commutative law for addition) \(\forall\, a,b\in\mathbb{R},\ a+b=b+a.\)

(P5) (Associative law for multiplication)  \(\forall\,a,b,c\in\mathbb{R},\ a\cdot(b\cdot c) = (a\cdot b)\cdot c.\)

(P6) (Existence of a multiplicative identity) \[\exists\, 1\in\mathbb{R}\setminus\{0\}, \forall\, a\in\mathbb{R},\ a\cdot 1 = 1\cdot a = a.\]

(P7) (Existence of multiplicative inverses) \[\forall\, a\in\mathbb{R}\setminus\{0\},\ \exists\, a^{-1}\in\mathbb{R},\ a\cdot a^{-1} = a^{-1}\cdot a = 1.\]

(P8) (Commutative law for multiplication) \(\forall\, a,b\in\mathbb{R},\ a\cdot b = b\cdot a.\)

(P9) (Distributive law) \(\forall\,a,b,c\in\mathbb{R},\ a\cdot(b+ c) = a\cdot b + a\cdot c.\)

Notation

Zero:

  • We will see shortly that the additive identity is unique.
  • Thus, we can talk about the additive inverse, also known as zero, and denoted \(0\).

Subtraction:

  • We will see shortly that additive inverses are unique, thus we can talk about the additive inverse \(-a\) of any real number \(a\).
  • Instead of \(a+(-a)\) we will write \(a-a\).
  • More generally, instead of \(a+(-b)\) we will write \(a-b\). 

Division:

  • Similarly, multiplicative inverses are unique, thus we can talk about the multiplicative inverse \(a^{-1}\) of any real number \(a\).
  • Instead of \(a\cdot b^{-1}\) we will often write \(\frac{a}{b}\) or \(a/b\). 

Some consequences:

Proposition 1. The additive identity in \(\mathbb{R}\) is unique.

Proof. Suppose \(0\) and \(0'\) are additive identities in \(\mathbb{R}\). Then, we have both \[0+0' = 0\quad\text{and}\quad 0+0' = 0'.\]

From this we conclude \(0=0'\). \(\Box\)

Proposition 2. The additive inverses in \(\mathbb{R}\) are unique.

This can be restated:

For all \(a,b,c\in\mathbb{R}\), if \(a+b=0\) and \(a+c=0\), then \(b=c\).

But in math we usually omit that universal quantifier and just write

If \(a+b=0\) and \(a+c=0\), then \(b=c\).

Proof. Suppose \(a,b,c\) are real numbers such that \(a+b=0\) and \(a+c=0\). Note that

\[b = b+0 = b+a-a = 0 -a = a+c - a = a-a+c = 0+c = c.\]

Proposition 3. If \(a\in\mathbb{R}\), then \(0\cdot a = 0\).

 

Try it yourself!

 

 

Proof. Let \(a\in\mathbb{R}\) be arbitrary. Note that

\[0\cdot a = 0\cdot a + 0\cdot a - 0\cdot a = (0+0)\cdot a - 0\cdot a = 0\cdot a - 0\cdot a = 0.\ \Box\]

 

Did you really try?

(because you're about to see my proof)

 

Math 600 Winter 2025

By John Jasper

Math 600 Winter 2025

  • 13